Country and industry equity risk premia in the euro area: an intertemporal approach - Lorenzo Cappiello; Marco Lo Duca; Angela Maddaloni (European Central Bank (ECB), 2008)
This paper provides new evidence on the dynamics of equity risk premia in euro area stock markets across country and industry portfolios. We develop and estimate a conditional intertemporal CAPM where returns on aggregate euro area, country and industry portfolios depend on the market risk as well as on the risk that the investment opportunity set changes over time. Prices of risks are time-varying, according to a Kalman filter approach. We find that both market and intertemporal risks are significantly priced. When we include country and industry-specific risk factors they turn out to be not significantly priced for most industries, suggesting that euro area equity markets are well integrated. Overall, the analysis indicates that omitting the intertemporal factor leads to mispricing and misleading conclusions regarding the degree of financial integration across sectors and countries.
Keywords: G12; F37; C32; 330; conditional asset pricing; financial integration; intertemporal risk; Kalman filter; multivariate GARCH; Aktie; Risikoprämie; CAPM; ARCH-Modell; Zustandsraummodell; Eurozone; Deutschland; Frankreich; Italien; Niederlande; Spanien